International Newsletter The Names Project. (San Francisco : The Names Project Foundation, 1988)
Fonds Suzan Daniel (FSD)
Periodiciteit : halfjaarlijks
Redactie : PO Box 14573, San Francisco, CA 94114
Engels
Periodiek